Doping Induced Optical Band Gap Modification of Potassium Dihydrogen Phosphate - Padmanabhan, Vijeesh; Majeed, Muneer E.; Kizhakkethil, Shifa; Vijayakumar, Arjun; Rajachandran, Vineeth (Current Physical Chemistry, 2024)
Aim: Potassium dihydrogen phosphate (KDP) is an excellent nonlinear optical material that has many potential applications, such as laser frequency conversion, Qswitches, Pockels cells, 3-D optical data storage devices, etc. Doping enhances various optical parameters of KDP. Doping changes in the absorbance and dopants such as aspartic acid, succinic acid, glycine, and L-alanine improved the optical band gap of the sample. Background: KDP is a non-linear optic material that has many important applications. Many researchers all over the world are trying to improve its optical properties. Objective: To synthesise pure KDP and KDP doped with aspartic acid, succinic acid, glycine, and L-alanine. Also, to study the temperature stability of the grown samples using TGA, DTA, and DSC analysis. Methods: Growth from solution at low temperatures is used for the growth of crystals. TGA, DTA, and DSC are used to analyse the stability of the samples against temperature variations. Results: KDP crystals of good quality were grown using the slow cooling solution growth technique. Determined their band gap using the Tauc Plot. Significant variations in the optical bandgap are noticed. Also, the TGA, DTA, and DSC characterizations were done. Conclusion: KDP solution and grown crystals of good quality were synthesized. The variation in the bandgap on doping is a significant result as the modifications in bandgap enable the sample to be used in a more enhanced applications. Also, the doped samples were stable for variations in temperature, like the pure KDP.
Keywords: potassium dihydrogen phosphate